Skydome Acoustical model - Bamford, Jeffery S. (Canadian Acoustics, 1999)
In 1996, Engineering Harmonics was retained to investigate, test and re-tune the current sound system for Toronto's SkyDome. On the basis of this work and insight into the sound system, in 1997 SkyDome retained Engineering Harmonics again to prepare cost estimates and a plan to upgrade the systems. After receiving approval, Engineering Harmonics began a project to upgrade, replace and improve the system. This project involved the replacement and addition of loudspeakers, replacement of amplifiers and implementation of a digital audio transportation and DSP system. This article discusses the EASE computer model that was used to model the new loudspeakers for the lower two tiers of seating.